Building democracy with women. Reflecting on experience in Latin America and the Caribbean / Ana María Brasileiro - Brasileiro, Ana María (1996)
Democrady and the women´s movement in latin America and the Caribbean, towards an engendered democracy; women´s political participation in the Dominican Republic, demanding the right to have rights, legislative change in Brazil and Paraguay, gender and justice administration in Ecuador, women´s human rights and dthe police, an andean regona seminar,engagement and empowerment in Grenada and Trinidad/Tobago, the mexican family, women and democracy.